2019
DOI: 10.21831/cp.v38i2.21821
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Social Capital in Disaster Management of Disaster Vulnerable Village Community on the Merapi Eruption

Abstract: Community resilience to anticipate disaster depends on the possession of social capital that grows in the community. Social capital can produce positive effects, unfortunately, disaster mitigations have been dominated by the development of human capital skills than social capital skills. This study aims to determine the role of social capital in disaster management in the disaster vulnerable communities of the Merapi Mount, taking a case in Girikerto village, Turi Sub-district, Sleman Regency, Special Province… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
3

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 14 publications
0
7
0
3
Order By: Relevance
“…Social capital contributes positively to the development of disaster-resistant communities even though its existence is not realized in social life. The values and norms in joint activities have also been reported to be based on togetherness, mutual assistance, care, and karmic legal mechanisms (Tohani & Wibawa, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Social capital contributes positively to the development of disaster-resistant communities even though its existence is not realized in social life. The values and norms in joint activities have also been reported to be based on togetherness, mutual assistance, care, and karmic legal mechanisms (Tohani & Wibawa, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Oleh karena itu modal sosial merupakan potensi yang harus dipahami, dieksplorasi, dikuatkan dan dijaga agar bermanfaat dalam kehidupan. Modal sosial memiliki manfaat yang mencakup: (a) bonding, yaitu ikatan antar individu dalam situasi rutin yang sama dan dekat, (b) bridging, yaitu ikatan dari beberapa orang yang lebih luas dan (c) linking, yaitu ikatan orang-orang di luar komunitas yang dapat mendorong individu untuk dapat memanfaatkan sumber daya yang sebanyak-banyaknya (Field, 2005;Tohani & Wibawa, 2019 Ada 5 jenis kesenian sebagai potensi budaya utama yang dimiliki dan di tampilkan secara bergantian pada saat ekpo berlangsung. Desa Deyangan menampilkan tiga grup kesenian, dan Desa Krinjing menampilkan dua grup kesenian.…”
Section: Metode Pelaksanaanunclassified
“…In the Merapi eruption case, the role of social capital in disaster-prone village communities lies on the elements of values and norms, commitment, trust, networking and information or knowledge-sharing (Tohani and Wibawa 2019). Jovita et al (2019) synthesizing the work of Macrae and Hodgkin (2011), Miyaguchi and Shaw (2007) and Pierre-Louis (2011), found that disaster resilience was associated with social capital in the form of connectiveness within the community, means of communication, dissemination of information and organizational interventions of nongovernmental actors.…”
Section: Literature Reviewmentioning
confidence: 99%